Photocatalyst based on longitudinal-transverse double seebeck effect thermoelectric substrate and preparation method and application thereof

By spin-coating TiO2-In2O3@g-C3N4 ternary composite photocatalyst on a thermoelectric matrix based on the longitudinal-transverse double Seebeck effect, the dual thermoelectric field effect of the thermoelectric matrix is ​​used to solve the challenges of photocatalytic materials in carrier separation and charge transport, and efficient photocatalytic performance improvement is achieved.

CN119897140AActive Publication Date: 2025-04-29SHAANXI UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510056033.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-29
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

Existing photocatalytic materials have challenges in improving photocatalytic efficiency, especially the efficient separation of carriers and charge transport, requiring the assistance of external drive sources.

Method used

Using a highly textured thermoelectric matrix based on the longitudinal-transverse double Seebeck effect, the separation and transportation of photogenerated carriers are regulated by spin-coating TiO2-In2O3@g-C3N4 ternary composite photocatalyst on its surface.

Benefits of technology

It significantly improves the catalytic performance of the photocatalyst, improves the separation efficiency and life of photogenerated carriers, reduces the recombination rate, and does not require additional field strength to meet the green and environmental protection needs of the energy industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a photocatalyst based on a longitudinal-transverse double Seebeck effect thermoelectric substrate as well as a preparation method and application of the photocatalyst. The photocatalyst comprises a thermoelectric substrate and a TiO2-In2O3 (at) g-C3N4 ternary composite photocatalyst loaded on the surface of the thermoelectric substrate, and the material of the thermoelectric substrate is highly textured Bi2Te2. 7Se0. 3. According to the method, the photocatalytic material is spin-coated on the substrate with the transverse thermoelectric effect, an additional device does not need to be introduced, and the catalytic performance of the catalyst can be remarkably optimized through the double thermoelectric field effect of the substrate. In addition, TiO2, In2O3 and g-C3N4 construct a heterojunction, and a formed built-in electric field effectively regulates and controls transportation of photon-generated carriers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermoelectric material applications, and relates to a highly textured photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix capable of enhancing photocatalytic effects, and a preparation method and application thereof. Background Art

[0002] Photocatalytic technology has developed into a relatively complete and mature system, which not only involves multidisciplinary research such as catalytic chemistry, photoelectrochemistry, semiconductor physics, materials science, and environmental science, but also has made significant progress in the design and control of catalytic materials. A large number of excellent semiconductor photocatalysts have emerged one after another, and various engineering strategies have continued to develop. Although these innovative achievements have made significant contributions to the construction of efficient photocatalytic systems, there are still some challenges in improving the efficiency of photocatalysis. For example, the ability of unconventional photocatalytic materials to generate and transfer photoinduced carriers is limited by their inherent properties. Therefore, it is necessary to find new external driving sources to promote the efficient separation of carriers, improve charge transport, and improve the comprehensive catalytic performance of photocatalysis.

[0003] The Chinese patent application with publication number CN114749169A improves the degradation ability of the catalyst by loading the photocatalyst on the thermoelectric rod; the Chinese patent application with publication number CN116550381A loads the thermoelectric material and the photocatalyst on the ciliary array substrate by the method of magnetic field induced self-assembly to achieve the effect of enhancing the degradation ability of the catalyst. However, the preparation process of the above-mentioned technology is relatively complicated and requires the additional assistance of a magnetic field to achieve the purpose of improving the photocatalytic performance. Therefore, exploring an external field-assisted enhanced photocatalytic technology with a simple preparation process and no need to introduce additional energy will directly or indirectly change the research in the field of photocatalysis based on the original redox reaction. Summary of the invention

[0004] In order to fill the gap in the field of enhanced photocatalysis by external field without external field strength, the purpose of the present invention is to provide a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix and a preparation method and application thereof.

[0005] The present invention is achieved through the following technical solutions: A photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix, comprising a thermoelectric matrix and a TiO2-In2O3@g-C3N4 ternary composite photocatalyst loaded on the surface of the thermoelectric matrix, wherein the thermoelectric matrix is ​​made of highly textured Bi2Te 2.7 Se 0.3 .

[0006] Preferably, the loading amount of TiO2-In2O3@g-C3N4 ternary composite photocatalyst on the thermoelectric substrate is 10-20 mg / cm 2 .

[0007] The method for preparing the photocatalyst based on the longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention comprises the following steps: S1, TeO2, BiCl3, NaSeO3 as raw materials, added to the solvent, solvothermal reaction to obtain Bi2Te 2.7 Se 0.3 Thermoelectric powder; Bi2Te 2.7 Se 0.3 The thermoelectric powder is subjected to spark plasma sintering to obtain a thermoelectric matrix; S2, adding g-C3N4 powder into ethanol, ultrasonically dispersing, adding tetrabutyl titanate and indium nitrate, and performing a solvothermal reaction to obtain a TiO2-In2O3@g-C3N4 ternary composite photocatalyst; S3, mixing TiO2-In2O3@g-C3N4 and a conductive binder in ethanol to obtain a catalyst emulsion; coating the catalyst emulsion on a thermoelectric substrate, and obtaining a photocatalyst based on a longitudinal-transverse double Seebeck effect thermoelectric substrate after standing and drying.

[0008] Preferably, in S1, the temperature of the solvothermal reaction is 180-200°C and the time is 24-36 h.

[0009] Preferably, in S1, the spark plasma sintering temperature is 380-410° C., the pressure is 45-50 MPa, and the time is 8-10 min.

[0010] Preferably, in S2, the ratio of g-C3N4, tetrabutyl titanate and indium nitrate is: 0.5 g: (0.2~0.4) mL: (0.5~1) mmoL.

[0011] Preferably, in S2, the temperature of the solvent thermal reaction is 150-200° C. and the time is 10-15 h.

[0012] Preferably, in S3, the conductive adhesive is PEDOT:PSS.

[0013] The present invention also provides the use of the photocatalyst based on the longitudinal-transverse dual Seebeck effect thermoelectric matrix in photocatalytic degradation of organic pollutants.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention is based on a photocatalyst of a thermoelectric substrate with a longitudinal-lateral dual Seebeck effect, and a TiO2-In2O3@g-C3N4 ternary composite photocatalyst is coated on the surface of a highly textured thermoelectric substrate to form a layer of photocatalyst coating on the surface of the thermoelectric substrate. Compared with low-oriented thermoelectric materials with traditional thermoelectric effects, highly textured thermoelectric materials have a transverse and longitudinal composite dual thermoelectric field effect. Its introduction can provide a powerful self-supplied dual thermoelectric field based on environmental waste heat for the photocatalyst, so that the carriers inside the thermoelectric substrate move in a directional manner according to the Seebeck effect, and the longitudinally moving carriers provide additional carrier support for the redox reaction of the photocatalyst. On this basis, the carriers transported laterally provide a vertical external electric field to the catalyst, thereby improving the separation efficiency of the photogenerated carriers of the catalyst, further extending the life of the photogenerated carriers and reducing their recombination rate. Therefore, the present invention can significantly optimize the catalytic performance of the catalyst by spin-coating the photocatalytic material on a substrate with a transverse thermoelectric effect without introducing additional devices, and the dual thermoelectric field effect existing in the substrate itself can significantly optimize the catalytic performance of the catalyst. In addition, TiO2, In2O3 and g-C3N4 construct a heterojunction, and the built-in electric field formed effectively regulates the transport of photogenerated carriers; in summary, the present invention can expand the results of catalyst redox reactions, improve the utilization efficiency in sewage degradation, carbon dioxide reduction, etc., and meet the development needs of green and environmental protection in the energy industry.

[0015] The invention discloses a method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix, which has a simple process flow and is pollution-free in production.

[0016] When the photocatalyst based on the longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention is used for photocatalysis, under light conditions, the upper surface of the highly textured thermoelectric matrix with transverse and longitudinal composite dual thermoelectric field effects absorbs heat so that there is a temperature difference with the lower surface, and then a transverse and longitudinal dual thermoelectric field is generated to achieve the effect of regulating the separation of photogenerated carriers on the catalyst surface. No external field strength is required, thus meeting the development needs of the green and environmentally friendly energy industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 Bi2Te prepared in Example 1 2.7 Se 0.3 X-ray diffraction patterns of powders and bulk; Figure 2 Bi2Te prepared in Example 1 2.7 Se0.3 Microstructure of the surface and cross section of the block under scanning electron microscope; Figure 3 This is a SEM image of TiO2-In2O3@g-C3N4 prepared in Example 1 at 13 k magnification under a field emission scanning electron microscope; Figure 4 This is the EDS spectrum of the TiO2-In2O3@g-C3N4 ternary composite photocatalyst prepared in Example 1; Figure 5 Thermoelectric substrate Bi2Te prepared in Example 1 2.7 Se 0.3 And the actual pictures of glass substrates loaded with TiO2-In2O3@g-C3N4 respectively; Figure 6 Thermoelectric substrate Bi2Te prepared in Example 1 2.7 Se 0.3 And the schematic diagram of the device for the photocatalytic reaction of glass control substrates loaded with TiO2-In2O3@g-C3N4 respectively; Figure 7 Thermoelectric substrate Bi2Te obtained in Example 1 2.7 Se 0.3 And the degradation curves of TiO2-In2O3@g-C3N4 loaded on the glass matrix after photocatalytic reaction in RhB solution. DETAILED DESCRIPTION

[0019] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0020] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0021] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0022] The photocatalyst based on the longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention comprises a thermoelectric matrix and a TiO2-In2O3@g-C3N4 ternary composite photocatalyst loaded on the surface of the thermoelectric matrix, wherein the material of the thermoelectric matrix is ​​highly textured Bi2Te 2.7 Se 0.3 .

[0023] In the present invention, the loading amount of TiO2-In2O3@g-C3N4 ternary composite photocatalyst on the thermoelectric substrate is preferably 10-20 mg / cm 2 , preferably 15 mg / cm 2 .

[0024] The present invention coats the TiO2-In2O3@g-C3N4 ternary composite photocatalyst on Bi2Te 2.7 Se 0.3 The surface of the thermoelectric substrate forms a photocatalyst coating on the surface of the thermoelectric substrate. 2.7 Se 0.3 The invention has the advantages of thinner and larger lamellae in microstructure. Compared with low-oriented thermoelectric materials with traditional thermoelectric effect, its powder after plasma spark sintering has high texturing, which brings it a dual thermoelectric field effect of horizontal and vertical composite. The introduction of thermoelectric matrix with dual thermoelectric field effect can provide a powerful self-supplied dual thermoelectric field based on environmental waste heat for the photocatalyst, so that the carriers inside the thermoelectric matrix can move in a directional manner according to the Seebeck effect. The carriers moving vertically provide additional carrier support for the redox reaction of the photocatalyst. On this basis, the carriers transported laterally provide a vertical external electric field to the catalyst, thereby improving the separation efficiency of the photogenerated carriers of the catalyst, further extending the life of the photogenerated carriers and reducing their recombination rate. In addition, compared with a single catalyst, TiO2, In2O3 and g-C3N4 are composited to construct a heterojunction, and the built-in electric field formed effectively regulates the transport of photogenerated carriers. The above factors all enhance the catalytic performance of the catalyst. Compared with the existing thermoelectric enhanced photocatalytic device, the improvement effect of the invention is better.

[0025] The method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention comprises the following steps: S1, TeO2, BiCl3, NaSeO3 as raw materials, added to the solvent, solvothermal reaction to obtain Bi2Te 2.7 Se 0.3 Thermoelectric powder; Bi2Te 2.7 Se 0.3 The thermoelectric powder is subjected to spark plasma sintering to obtain a thermoelectric matrix; S2, adding g-C3N4 powder into ethanol, ultrasonically dispersing, adding tetrabutyl titanate and indium nitrate, and performing a solvothermal reaction to obtain a TiO2-In2O3@g-C3N4 ternary composite photocatalyst; S3, mixing TiO2-In2O3@g-C3N4 and a conductive binder in ethanol to obtain a catalyst emulsion; coating the catalyst emulsion on a thermoelectric substrate, and obtaining a photocatalyst based on a longitudinal-transverse double Seebeck effect thermoelectric substrate after standing and drying.

[0026] In the preparation method of the photocatalyst based on the vertical-horizontal dual Seebeck effect thermoelectric matrix of the present invention, the Bi2Te 2.7 Se 0.3 The size of the nanosheets can be controlled by changing the sintering temperature, pressure and mold diameter of spark plasma sintering to adjust the Bi2Te 2.7 Se 0.3 densification and texturing. Specifically, the temperature of the solvothermal reaction is 180~200℃, and the time is 24~36 h. The temperature of spark plasma sintering is 380~410℃, the pressure is 45~50 MP, the time is 8~10 min, and the mold diameters used are 12 mm and 20 mm.

[0027] In the preparation method of the photocatalyst based on the longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention, the catalytic effect of the ternary composite photocatalyst can be adjusted by changing the molar ratio of g-C3N4, tetra-n-butyl titanate and indium nitrate. Specifically, the ratio of g-C3N4, tetra-n-butyl titanate and indium nitrate is 0.5 g: (0.2~0.4) mL: (0.5~1) mmoL.

[0028] In S2 of the method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention, the temperature of the solvent thermal reaction is 150-200° C. and the time is 10-15 hours.

[0029] In S3 of the method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention, the conductive adhesive is PEDOT:PSS, and the volume ratio of the PEDOT:PSS to ethanol is 1:(40-50).

[0030] In S3 of the method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention, coating is specifically performed by spin coating using a spin coater, and the pre-rotation speed of the spin coater is 700-1000 r / min and the positive rotation speed is 1500-2000 r / min.

[0031] The photocatalyst based on the longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention can be used as a photocatalyst material for photocatalytic degradation of organic pollutants. Compared with other external field enhanced photocatalytic effects, the present invention does not require the introduction of additional electric field or magnetic field devices. The thermoelectric matrix as a photocatalyst matrix can establish its own upper and lower surface temperature difference through waste heat in the environment and then generate a thermoelectric field, regulate the separation of photogenerated carriers of the photocatalyst on the surface of the thermoelectric matrix, and achieve the effect of self-powered auxiliary enhancement of the photocatalyst.

[0032] Example 1 A method for preparing a highly textured photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix that can enhance the photocatalytic effect comprises the following steps: 1) Preparation of highly textured thermoelectric substrates TeO2, BiCl3, and NaSeO3 were used as raw materials and the solvent thermal reaction was carried out in ethylene glycol at 180 °C for 24 h to obtain Bi2Te 2.7 Se 0.3 Thermoelectric powder; using spark plasma sintering (SPS) technology, Bi2Te 2.7 Se 0.3 The thermoelectric powder was sintered at 380℃ and 45 MPa for 8 min to prepare a bulk thermoelectric matrix with a diameter of 20 mm. 2) Preparation of TiO2-In2O3@g-C3N4 ternary composite photocatalyst 20 g of urea was dissolved in 20 mL of deionized water at 50°C, and then heated in a muffle furnace at 550°C for 4 h to obtain g-C3N4. After washing with water, washing with alcohol, and drying in an oven at 60°C for 24 h, bright yellow graphite phase C3N4 powder was obtained. 0.5 g of graphite phase C3N4 powder was taken, and ultrasonic dispersion was performed in 40 mL of ethanol for 30 min. Then, Ti source and In source were introduced by adding 0.2 mL of tetra-n-butyl titanate and 0.5 mmol indium nitrate. After hydrothermal reaction at 180°C for 12 h, the powder was centrifuged, washed with water, washed with alcohol, and dried to obtain TiO2-In2O3@g-C3N4 ternary composite photocatalyst powder. 3) Preparation of photocatalyst based on vertical-horizontal dual Seebeck effect thermoelectric matrix PEDOT:PSS was selected as the conductive adhesive for the thermoelectric substrate and the photocatalyst. TiO2-In2O3@g-C3N4 was placed in a mixed solution of PEDOT:PSS and ethanol (the volume ratio of PEDOT:PSS to ethanol was 1:40) and crushed in a cell crusher for 6 h to obtain a catalyst emulsion in which the photocatalyst was uniformly dispersed. The pre-speed of the spin coater was set to 1000 r / min and the positive speed was set to 2000 r / min. The catalyst emulsion was evenly coated on the Bi2Te 2.7 Se 0.3 After standing and drying for 5 hours, a photocatalyst based on the longitudinal-transverse double Seebeck effect thermoelectric matrix was obtained.

[0033] Example 2 1) Preparation of highly textured thermoelectric substrates TeO2, BiCl3, and NaSeO3 were used as raw materials and the solvent thermal reaction was carried out in ethylene glycol at 190 °C for 30 h to obtain Bi 0.5 Sb 1.5 Te3 thermoelectric powder, using spark plasma sintering (SPS) technology, Bi2Te 2.7 Se 0.3 The thermoelectric powder was sintered at 390℃ and 47 MPa for 8 min to prepare a thermoelectric block with a diameter of 20 mm. 2) Preparation of TiO2-In2O3@g-C3N4 ternary composite photocatalyst 20 g of urea was dissolved in 20 mL of deionized water at 50 °C, and then heated in a muffle furnace at 550 °C for 4 h to obtain g-C3N4. After washing with water, washing with alcohol, and drying in an oven at 60 °C for 24 h, bright yellow graphite phase C3N4 powder was obtained. 0.5 g of graphite phase C3N4 powder was taken, added with 40 mL of ethanol and ultrasonically dispersed for 30 min, and then 0.3 mL of tetra-n-butyl titanate and 0.7 mmol indium nitrate were added to introduce Ti and In sources. After hydrothermal reaction at 180 °C for 12 h, the powder was centrifuged, washed with water, washed with alcohol, and dried to obtain TiO2-In2O3@g-C3N4 ternary composite photocatalyst powder. 3) Preparation of photocatalyst based on vertical-horizontal dual Seebeck effect thermoelectric matrix PEDOT:PSS was selected as the conductive adhesive for the thermoelectric substrate and the photocatalyst. TiO2-In2O3@g-C3N4 was placed in a mixed solution of PEDOT:PSS and ethanol (the volume ratio of PEDOT:PSS to ethanol was 1:44) and crushed in a cell crusher for 3 h to obtain an emulsion in which the catalyst was evenly dispersed. The pre-speed of the spin coater was set to 700 r / min and the positive speed was set to 1500 r / min. The catalyst emulsion was evenly coated on the Bi2Te 2.7 Se 0.3 On the thermoelectric substrate, after standing and drying for 5 hours, a photocatalyst based on the longitudinal-transverse double Seebeck effect thermoelectric substrate was obtained.

[0034] Example 3 1) Preparation of highly textured thermoelectric substrates Bi2Te was obtained by solvothermal reaction of TeO2, BiCl3 and NaSeO3 in ethylene glycol at 195 °C for 33 h. 2.7 Se 0.3 Thermoelectric powder, using spark plasma sintering (SPS) technology, Bi2Te 2.7 Se 0.3 The thermoelectric powder was sintered at 400℃ and 49 MPa for 8 min to prepare a thermoelectric block with a diameter of 20 mm. 2) Preparation of TiO2-In2O3@g-C3N4 ternary composite photocatalyst 20g of urea was dissolved in 20mL of deionized water at 50℃, and then heated in a muffle furnace at 550℃ for 4h to obtain g-C3N4. After washing with water, washing with alcohol, and drying in an oven at 60℃ for 24h, bright yellow graphite phase C3N4 powder was obtained. 0.5g of graphite phase C3N4 powder was taken, added with 40mL of ethanol and ultrasonically dispersed for 30min, and then 0.35mL of tetra-n-butyl titanate and 0.8mmol of indium nitrate were added to introduce Ti source and In source. After hydrothermal reaction at 180℃ for 12h, the powder was centrifuged, washed with water, washed with alcohol, and dried to obtain TiO2-In2O3@g-C3N4 ternary composite photocatalyst powder. 3) Preparation of photocatalyst based on vertical-horizontal dual Seebeck effect thermoelectric matrix PEDOT:PSS was selected as the conductive adhesive for the thermoelectric substrate and the photocatalyst. TiO2-In2O3@g-C3N4 was placed in a mixed solution of PEDOT:PSS and ethanol (the volume ratio of PEDOT:PSS to ethanol was 1:48), and the mixture was crushed in a cell crusher for 4 h to obtain an emulsion in which the catalyst was evenly dispersed. The pre-speed of the spin coater was set to 800 r / min and the positive speed was set to 1700 r / min. The catalyst emulsion was evenly coated on the Bi2Te 2.7 Se0.3 On the thermoelectric substrate, after standing and drying for 5 hours, the thermoelectric substrate loaded with ternary photocatalyst was obtained.

[0035] Example 4 1) Preparation of highly textured thermoelectric substrates Bi2Te was obtained by solvothermal reaction of TeO2, BiCl3 and NaSeO3 in ethylene glycol at 200℃ for 36 h. 2.7 Se 0.3 Thermoelectric powder, using spark plasma sintering (SPS) technology, Bi2Te 2.7 Se 0.3 The thermoelectric powder was sintered at 410℃ and 50 MPa for 8 min to prepare a block of thermoelectric matrix with a diameter of 20 mm. 2) Preparation of TiO2-In2O3@g-C3N4 ternary composite photocatalyst 20g of urea was dissolved in 20mL of deionized water at 50℃, and then heated in a muffle furnace at 550℃ for 4h to obtain g-C3N4. After washing with water, washing with alcohol, and drying in an oven at 60℃ for 24h, bright yellow graphite phase C3N4 powder was obtained. 0.5g of graphite phase C3N4 powder was taken, added with 40mL of ethanol and ultrasonically dispersed for 30min, and then 0.4mL of tetra-n-butyl titanate and 1 mmol of indium nitrate were added to introduce Ti source and In source. After hydrothermal reaction at 180℃ for 12h, the powder was centrifuged, washed with water, washed with alcohol, and dried to obtain TiO2-In2O3@g-C3N4 ternary composite photocatalyst powder. 3) Preparation of photocatalyst based on vertical-horizontal dual Seebeck effect thermoelectric matrix PEDOT:PSS was selected as the conductive adhesive for the thermoelectric substrate and the photocatalyst. TiO2-In2O3@g-C3N4 was placed in a mixed solution of PEDOT:PSS and ethanol (the volume ratio of PEDOT:PSS to ethanol was 1:50), and the mixture was crushed in a cell crusher for 5 h to obtain an emulsion in which the catalyst was evenly dispersed. The pre-speed of the spin coater was set to 900 r / min and the positive speed was set to 1800 r / min. The catalyst emulsion was evenly coated on the Bi2Te 2.7 Se 0.3 On the thermoelectric substrate, after standing and drying for 5 hours, a photocatalyst based on the longitudinal-transverse double Seebeck effect thermoelectric substrate was obtained.

[0036] The X-ray diffraction of the thermoelectric powder and the block after spark plasma sintering prepared in Example 1 of the present invention is as follows: Figure 1 As shown, it can be seen that the diffraction peaks are consistent with the bismuth telluride PDF card, and the orientation of the block after heating and pressure sintering is enhanced along the (001) direction. 2.7 Se0.3 The cross-sectional SEM image of the thermoelectric substrate is shown in Figure 2 As shown, it can be seen that its layered structure is obvious and the degree of texturing is high.

[0037] Figure 3 The SEM image of the TiO2-In2O3@g-C3N4 ternary composite photocatalyst with photocatalytic effect obtained in Example 1 shows that its microstructure is loose and porous. Figure 4 It can be seen from the EDS spectrum that TiO2 and In2O3 particles are successfully composited on the g-C3N4 surface and the elements are evenly distributed.

[0038] Samples of photocatalysts based on vertical-horizontal dual Seebeck effect thermoelectric matrix with enhanced photocatalytic effect such as Figure 5 As shown, the TiO2-In2O3@g-C3N4 ternary composite photocatalyst is uniformly loaded on the glass substrate (a) and the thermoelectric substrate (b).

[0039] Figure 6 This is a diagram of the photocatalytic degradation reaction of Rhodamine B by the photocatalyst based on the longitudinal-transverse dual Seebeck effect thermoelectric matrix with enhanced photocatalytic effect obtained in Example 1 and the test device. Figure 7 The photocatalytic degradation curve (a) and kinetic curve (b) of Rhodamine B by the photocatalyst based on the longitudinal-transverse double Seebeck effect thermoelectric matrix with enhanced photocatalytic effect obtained in Example 1 and the glass matrix-loaded photocatalyst composite material show that, compared with the 19% degradation rate of the photocatalyst loaded on the glass control matrix, the degradation rate of RhB by the TiO2-In2O3@g-C3N4 ternary composite photocatalyst loaded on the thermoelectric matrix reached 32% after 60 min. This shows that the thermoelectric matrix effectively improves the catalytic performance of the photocatalyst.

[0040] In summary, the method for preparing a highly textured photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix of the present invention, the obtained photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix has an enhanced photocatalytic effect, and its catalytic performance is better than that of a photocatalyst loaded on a matrix without thermoelectric effect. Compared with other external field-assisted enhanced photocatalysis, the thermoelectric matrix in the present invention can generate an electric field through ambient temperature to achieve the effect of assisted enhanced photocatalysis, without the need for external field strength, thereby meeting the development needs of green and environmental protection in the energy industry.

Claims

1. A photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix, characterized in that: The invention comprises a thermoelectric substrate and a TiO2-In2O3@g-C3N4 ternary composite photocatalyst loaded on the surface of the thermoelectric substrate, wherein the material of the thermoelectric substrate is highly textured Bi2Te 2.7 Se 0.3 .

2. The photocatalyst based on the longitudinal-transverse dual Seebeck effect thermoelectric matrix according to claim 1, characterized in that: The loading amount of TiO2-In2O3@g-C3N4 ternary composite photocatalyst on the thermoelectric substrate is 10-20 mg / cm 2 .

3. The method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix according to claim 1 or 2, characterized in that: The following steps are involved: S1, TeO2, BiCl3, NaSeO3 as raw materials, added to the solvent, solvothermal reaction to obtain Bi2Te 2.7 Se 0.3 Thermoelectric powder; Bi2Te 2.7 Se 0.3 The thermoelectric powder is subjected to spark plasma sintering to obtain a thermoelectric matrix; S2, adding g-C3N4 powder into ethanol, ultrasonically dispersing, adding tetrabutyl titanate and indium nitrate, and performing a solvothermal reaction to obtain a TiO2-In2O3@g-C3N4 ternary composite photocatalyst; S3, mixing TiO2-In2O3@g-C3N4 and a conductive binder in ethanol to obtain a catalyst emulsion; coating the catalyst emulsion on a thermoelectric substrate, and obtaining a photocatalyst based on a longitudinal-transverse double Seebeck effect thermoelectric substrate after standing and drying.

4. The method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix according to claim 3, characterized in that: In S1, the temperature of the solvothermal reaction is 180~200℃ and the time is 24~36 h.

5. The method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix according to claim 3, characterized in that: In S1, the spark plasma sintering temperature is 380~410℃, the pressure is 45~50 MP, and the time is 8~10 min.

6. The method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix according to claim 3, characterized in that: In S2, the ratio of g-C3N4, tetrabutyl titanate and indium nitrate is: 0.5 g: (0.2~0.4) mL: (0.5~1) mmoL.

7. The method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix according to claim 3, characterized in that: In S2, the temperature of the solvent thermal reaction is 150~200℃ and the time is 10~15h.

8. The method for preparing a photocatalyst based on a longitudinal-transverse dual Seebeck effect thermoelectric matrix according to claim 3, characterized in that: In S3, the conductive adhesive is PEDOT:PSS.

9. Use of the photocatalyst based on the longitudinal-transverse dual Seebeck effect thermoelectric matrix as claimed in claim 1 or 2 in photocatalytic degradation of organic pollutants.

Citation Information

Patent Citations

  • Method for preparing bismuth selenide micron-tablet

    CN104528663A

  • Preparation method of hydrogen production by photolysis of water

    CN110116988A

  • Thermoelectric-based photocatalyst and preparation method and application thereof

    CN114749169A

  • Thermoelectric enhanced photocatalytic cilium array and preparation method thereof

    CN116550381A

  • Titanium dioxide loaded composite photocatalytic material and preparation method thereof

    CN117816214A